Pronunciation challenges: seventh-grade consonant errors in SMP PGRI Walantaka - Faidzin, Rama Nur; Sidik, Ezis Japar; Handayani, Ika (Jurnal Langua, 2024)
The study investigated the pronunciation errors made by seventh-grade students at SMP PGRI Walantaka Serang specifically on fricatives and affricates sounds. The research used qualitative methodology with case study as the research design, and the sample of this research was class VII with a total of 25 students as the participants. The data collecting technique used in this research was observation, interview, and documentation. The errors found were misformation errors with the presentation of 77,77% of total errors that students made, followed by addition with 11,11%, omission errors with 7,40%, and the lowest error was misordering error with 3,70%. The source of errors was because of the involvement of students’ native language and accents, challenges in adopting English pronunciation, insufficient facility, lack of teachers, and students’ learning styles, and teacher’s inaccuracy in communicating the subject. The researcher concludes that students struggle with pronunciation, specifically fricatives and affricates.